The effects of compression garments on intermittent exercise performance and recovery on consecutive days - Duffield, R.; Edge, J.; Merrells, R.; Hawke, E.; Barnes, M.; Simcock, D.; Gill, N. (International Journal of Sports Physiology and Performance, 2008)
Purpose: The aim of this study was to determine whether compression garments improve intermittent-sprint performance and aid performance or self-reported recovery from high-intensity efforts on consecutive days. Methods: Following familiarization, 14 male rugby players performed two randomized testing conditions (with or without garments) involving consecutive days of a simulated team sport exercise protocol, separated by 24 h of recovery within each condition and 2 weeks between conditions. Each day involved an 80-min high-intensity exercise circuit, with exercise performance determined by repeated 20-m sprints and peak power on a cart dynamometer (single-man scrum machine). Measures of nude mass, heart rate, skin and tympanic temperature, and blood lactate (La-) were recorded throughout each day; also, creatine kinase (CK) and muscle soreness were recorded each day and 48 h following exercise. Results: No differences (P = .20 to 0.40) were present between conditions on either day of the exercise protocol for repeated 20-m sprint efforts or peak power on a cart dynamometer. Heart rate, tympanic temperature, and body mass did not significantly differ between conditions; however, skin temperature was higher under the compression garments. Although no differences (P = .50) in La- or CK were present, participants felt reduced levels of perceived muscle soreness in the ensuing 48 h postexercise when wearing the garments (2.5 ± 1.7 vs 3.5 ± 2.1 for garment and control; P = .01). Conclusions: The use of compression garments did not improve or hamper simulated team-sport activity on consecutive days. Despite benefits of reduced self-reported muscle soreness when wearing garments during and following exercise each day, no improvements in performance or recovery were apparent.